Pulsed homogeneous orthogonal field gel electrophoresis (PHOGE). - Bancroft, I (1988)
A versatile system (PHOGE) has been developed that allows resolution of molecules of DNA megabase pair size by the use of homogeneous, orthogonal, pulsed fields. The resulting electrophoretograms have characteristics that differ from those produced by other systems for pulsed field electrophoresis. Molecules in a two-fold range of sizes can be separated with maximum resolution, or a much larger range of sizes may be separated with lower resolution but with a linear relationship of mobility to size from 50 kb, or below, to at least 1 Mb. Straight lanes and large useable gel areas, characteristic of PHOGE, are also valuable for mapping procedures or for any other circumstance in which large numbers of samples of DNA are to be directly compared. Existing models cannot explain the results obtained, because a stage of the molecular reorientation appears to result in a rate of migration greater than that occurring by reptation. We suggest a mechanism that might account for the resolution observed and also suggest that the resolution achieved by existing OFAGE-type systems may be the result of the superimposition of PHOGE and FIGE separatory mechanisms. No maximum size of molecules that may be resolved by the PHOGE system has yet been determined.